MASS STRANDING OF PILOT WHALES IN THE GULF OF MANNAR - Alagarswami, K; Bensam, P; Rajapandian, M E; Fernando, A Bastian (Indian Journal of Fisheries, 2011)
Many Indian pilot whales, Globicephala macrorhyncha, were stranded in ashallow bay in the Gulf-of Mannar at Manapad on 14 January 1973. This is the secondrecorded instance of stranding of pilot whales ou the Indian coasts, in which a casualty of147 individuals is involved; the earlier one was at Serampore on the Hooghly River.The dead whales had a size range "of 220-575 cm. General morphological and diagnosticskeletal features of the pilot whales are given and discussed. Autopsy andchemical examination proved neptive for the presence of poisonous substances in thetissues of the stranded animals. The mass stranding at Manapad is discussed withreference to similar phenomenon among the pilot whales noticed in other parts ofthe world